2022
DOI: 10.1080/14756366.2022.2086868
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of biodegradable sulphonamide candidates treating septicaemia by synergistic dual inhibition of COX-2/PGE2 axis and DHPS enzyme

Abstract: A new series of co-drugs was designed based on hybridising the dihydropteroate synthase (DHPS) inhibitor sulphonamide scaffold with the COX-2 inhibitor salicylamide pharmacophore through biodegradable linkage to achieve compounds with synergistic dual inhibition of COX-2/PGE2 axis and DHPS enzyme to enhance antibacterial activity for treatment of septicaemia. Compounds 5 b, 5j, 5n and 5o demonstrated potent in vitro COX-2 inhibitory activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In addition, indomethacin and diclofenac sodium were used as standard nonselective human COX inhibitors. The enzymatic assay was carried out according to a procedure in the literature [ 22 , 23 ] utilizing an ovine COX-1/human recombinant COX-2 assay kit (catalog no. 560131; Cayman Chemicals Inc., Ann Arbor, MI, USA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, indomethacin and diclofenac sodium were used as standard nonselective human COX inhibitors. The enzymatic assay was carried out according to a procedure in the literature [ 22 , 23 ] utilizing an ovine COX-1/human recombinant COX-2 assay kit (catalog no. 560131; Cayman Chemicals Inc., Ann Arbor, MI, USA).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro human COX-1 and human COX-2 enzymatic inhibitory activity of the tested compounds as well as the reference drugs was carried out according to the previously mentioned procedures [ 22 , 23 ]; for details, see Page S15, Supplementary File .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies using rodent models show that some algal derived components like carrageenan can induce intestinal inflammation, and to significantly alter gastrointestinal tract microbiota composition (Benard et al 2010;Chassaing et al 2017). Some algal based constituents like carrageenan are widely used to induce the innate immune response in animal models of inflammation, and points to the possibility of immune modifying properties for some algal species or constituents (Wei et al 2016;El-Dershaby et al 2022;Yi et al 2022). Indeed, several studies have reported inflammatory responses of human colonic epithelial cells to carrageenan (Borthakur et al 2007;Bhattacharyya et al 2008;Choi et al 2012).…”
Section: Discussionmentioning
confidence: 99%